Comparison of Birth Outcomes by Gestational Diabetes Screening Criteria - Davis, Esa M.; Scifres, Christina M.; Abebe, Kaleab; Costacou, Tina; Comer, Diane; Catalano, Patrick; Simhan, Hyagriv; Freiberg, Matthew; Day, Nancy (American Journal of Perinatology Reports, 2018)
Objectives This study is to examine the association between different diagnostic criteria for gestational diabetes mellitus (GDM) and adverse birth outcomes.Study Design A retrospective cohort study of 5,937 women with a singleton pregnancy was conducted, who completed GDM screening between 24 to 32 weeks gestational age. Four nonoverlapping groups of women defined as: 1) Normal: glucose challenge test (GCT) <130 mg/dL, 2) elevated GCT + normal oral glucose tolerance test (OGTT): abnormal 1 hour GCT + normal 3 hour OGTT, 3) GDM/International Association of Diabetes in Pregnancy Study Group (IADPSG): abnormal 3 hour OGTT by the IADPSG criteria, and 4) GDM/Carpenter-Coustan (CC): diagnosis per CC criteria. We used logistic regression to examine the association between GDM group classification and main outcome of macrosomia and secondary birth outcomes.Results Prevalences were GDM/CC 4.6%, GDM/IADPSG 3.0, and 7.6% overall. GDM/IADPSG group was associated with increased macrosomia (adj OR [odd ratio] 1.87; 95% CI [confidence interval]: 1.08–3.25; p = 0.02), while GDM/CC group was associated with increased preterm birth (adj OR 1.75; 95% CI: 1.05–2.80; p = 0.03).Conclusion Little difference in birth outcomes was found between the two criteria, GDM/CC and GDM/IADPSG. Randomized controlled trials are needed to clarify the risks and benefits of these screening paradigms before their incorporation into clinical practice.
Keywords: screening strategies; gestational diabetes; fetal growth; pregnancy outcomes